Lab-on-a-Chip Fabrication and Application - Stoytcheva, Margarita; Zlatev, Roumen (IntechOpen, 2016)
The necessity of on-site, fast, sensitive, and cheap complex laboratory analysis, associated with the advances in the microfabrication technologies and the microfluidics, made it possible for the creation of the innovative device lab-on-a-chip (LOC), by which we would be able to scale a single or multiple laboratory processes down to a chip format. The present book is dedicated to the LOC devices from two points of view: LOC fabrication and LOC application.